(untitled) (The Research of Medical Science Review, 2025)
This study investigated the seasonal and age-wise prevalence of Trichuris spp. in small ruminants within District Kohat, Khyber Pakhtunkhwa. A total of 400 fecal samples were collected from sheep and goats (200 each) across all tehsils in the region. Identification of Trichuris eggs was performed using microscopic techniques, including flotation and sedimentation, based on morphological characteristics. The overall prevalence was calculated, and the relationship with season and age was statistically analyzed using chi-square tests and t-tests, with significance set at p<0.05. The results revealed that the highest prevalence occurred during the monsoon season, significantly higher infection rates in adult animals (>18 months). Among sheep and goats, infection rates varied, with goats showing marginally higher prevalence. The study identified potential correlations between age and season with parasitic burden. These findings provide crucial epidemiological insights and suggest that control strategies should be targeted seasonally and age-specifically. The study underscores the importance of implementing timely anthelmintic protocols and enhancing farm-level hygiene practices to curb the spread of Trichuris infections. This epidemiological baseline is expected to guide future parasitic control strategies, contributing to improved health and productivity of small ruminants in the region.